I Love Indonesia: A Junior Encyclopedia for Early Childhood Education to Promote Local Culture Using Ethnopedagogy - Roudlotun Ni'mah; Endang Puspitasari; Siti Labiba Kusna (Journal of Islamic Education Students (JIES), 2024)
The rise device technology, making civilization the more faded, culture foreigners who enter without filter, start to displace culture local impact in education child age early, then required a medium for stimulate knowledge child about culture local around. Types of research This is research and development or Research and Development (R&D). Development model This ADDIE with steps development consists of on stages analyze, design, development, implementation, and evaluation. Study  This aiming  produce Encyclopedia  child  as  source  Study  through approach ethnopedagogic. Research This conducted at the Residency Bojonegoro. Subject  study is a teacher and child of group B of Mardiwiyata 2 Kindergarten, Tuban , RA Madinatul Ulum Bojonegoro, and ABA Kindergarten, Guno Lamongan For know  practicality and effectiveness Junior encyclopedia. Based on   results  study  obtained that  Encyclopedia child Based on local residency culture bojonegoro developed own  specifications with Kiritera quality (standard) of non- text books, and has fulfil criteria validity with  score (4.56), criteria  practicality  with score  teacher response (4.33) and response  students (4.21), and Effectiveness  with (84%), so that the Junior Encyclopedia media is based on local residency culture bojonegoro can used as Source Study.